HISTORICAL ORGANIZATION AND DEVELOPMENT PROCESSES OF ANCIENT STATES IN THE TERRITORY OF UZBEKISTAN - Ubaydullayev I. F (TARIXIY TADQIQOTLAR, 2025)
This article presents a comprehensive study of ancient state formation in the territory of present-day Uzbekistan from the 3rd century BCE to the 4th century CE. It explores the political, military, economic, cultural, and religious aspects of the Greco-Bactrian Kingdom, Kanhga, Davan, Tokharistan, and the Kushan Empire. The research also examines coinage systems, international trade routes, and the influence of these states on subsequent historical developments in Central Asia. The study is based on archaeological, numismatic, and historical sources.